HORIZONTAL MOTIONS AND PLATE BOUNDARIES IN SAKHALIN AND HOKKAIDO - Saprygin S.M.; Kononov V.E.; Senachin V.N. (My University, 2004)
The present communication is devoted to geological and instrumental data on horizontal motions in the deep zones of Sakhalin and Hokkaido. We have first established the existence of horizontal motions along two (north-northeastern and south-southeastern) directions in Sakhalin and substantiated the boundary between the Eurasian and Sea of Okhotsk plates. Taking into account the data of Japanese researchers on Hokkaido, one can assume that the Sea of Okhotsk Plate is undergoing anticlockwise rotation at a rate of up to 2 cm/yr.